The Role And Responsibilities of A Notary In Public Services Based on Professional Ethic Morals and Law - Widya Chandra, I Gusti Ayu; Novy Purwanto , I Wayan (Dinasti Research, 2024)
The purpose of this research is to determine the role of notaries and the responsibilities of notaries. This legal research uses empirical legal research and then uses a legislative approach and analysis of legal concepts as well as qualitative methods, the results of which are presented in a systematic qualitative descriptive manner. Based on the analysis, it is known that notaries play a role in providing services to the public in accordance with moral principles and professional ethics through authentic deeds as valid evidence. Notaries have the responsibility to provide services to the public in accordance with moral principles and professional ethics in accordance with the notary code of ethics in the UUJN, and other regulations.